Pemanfaatan Alokasi Dana Desa dalam Pembangunan Infrastruktur di Desa Pandu Kecamatan Cerme Kabupaten Gresik - Hendra Cyzar Pratama Saputra; Sri Wahyuni (Public Administration Dept, Faculty of Social and Political Science, 2022)
National development is an effort made by the government to develop the overall process of the state administration system and all aspects of people's lives to realize national goals. To help accelerate rural development, the government then provided the Village Fund Allocation (ADD) assistance program. The provision of Village Fund Allocations aims to be a stimulant and a stimulus for village growth. ADD assistance was also given to Pandu Village, Come District, Gresik Regency. The purpose of this study is to analyze the use of Village Fund Allocation in Infrastructure Development in Pandu Village, Cerme District, Gresik Regency, using a qualitative descriptive approach, using the theory of Rahardjo (2006) about the principle of village development. The results of this study indicate that infrastructure development in Pandu Village has been going well, but there are certain indicators that are still not optimally implemented, such as transparency indicators that have not been carried out by the village government to the community evenly. Indicators of participation are also not maximized in its implementation due to the desire of the people who do not participate in village development. Therefore, it is necessary to hold active socialization in the village community so that the community knows the activities carried out and the budget funds that have been issued, and it is necessary to evaluate each implementation of infrastructure development programs in order to increase community participation in Pandu Village so that it has a positive impact on the quality of community groups. in Pandu Village.